A systematic review and meta-analysis on the use of diagnostic ultrasound in guiding corticosteroid injections for shoulder pain (subacromial/ subdeltoid bursa) - Aamir Safdar Khan; Munir Khan; Muhammad Siddiqui; Amna Aamir Khan; Mubarra Rao (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the efficacy of diagnostic ultrasound-guided corticosteroid injections in subacromial/subdeltoid bursa in the management of shoulder pain. Method: The systematic review and meta-analysis was conducted from November 2023 to February 2024 in line with the Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines, and comprised search on Cochrane Central Register of Controlled Trials, Excerpta Medica dataBASE, Scopus and PubMed databases for randomised controlled and/or clinical trials involving adult patients with shoulder pain/subacromial impingement/bursitis, comparing ultrasound-guided corticosteroid injections versus blind injections, and published in the English language between January 2003 and August 2023. Quality assessment was performed using the Physiotherapy Evidence Database scale, and meta-analysis was performed using MedCalc software. Results: Of the 72 full-text articles assessed, 11(15.3%) were analysed. There was a definite short-term effectiveness of ultrasound-guided corticosteroid injections in reducing pain, as assessed by visual analogue scale scores (p <0.001 at 6 weeks; p<0.05 at 12 week and 33 week) and improved range of motion in flexion, abduction, internal and external rotation (p<0.001-0.05). While meta-analysis confirms significant pooled effects for pain scores and range of motion outcomes at 6 weeks, long-term efficacy remained inconclusive due to heterogeneity across studies and limited long-term follow-up research on the subject. Conclusion: Evidence supported short-term efficacy of ultrasound-guided corticosteroid injections for shoulder pain management, but robust trials with extended follow-up periods and larger cohorts are needed to establish their long-term effectiveness. Key Words: Ultrasonography, Interventional ultrasound, Shoulder pain, Corticosteroids, Shoulder impingement syndromes.